Applying a MTSS framework to address racism and promote mental health for racial/ethnic minoritized youth. Issue 12 (8th October 2021) - Malone, Celeste M.; Wycoff, Kirby; Turner, Erlanger A.
Abstract: Ample evidence suggests that PK‐12 students experience racism and other forms of discrimination in school and that these experiences have a deleterious impact on their mental health. Several studies have shown a consistent and strong relationship between racism and negative mental health outcomes including increased depression and anxiety, decreased self‐worth and self‐esteem, as well as psychological maladjustment. School‐based mental health services can ensure that racial and ethnic minoritized (REM) students gain access to mental health services. Because schools are one place where REM students experience structural and individual discrimination, it is critical that school‐based mental health providers utilize strategies to promote school climates that are safe and affirming for these students. Using a multitiered system of support framework, we describe the tier 1 interventions to promote positive school racial climate and the elements of culturally responsive practices to be integrated into tier 2 and tier 3 interventions to improve mental health outcomes for REM youth.